Effects of debulk temperature on air evacuation during vacuum bag-only prepreg processing. (2nd January 2020) - Hu, Wei; Nutt, Steven
Abstract: Air removal prior to cure is critical for limiting porosity during vacuum bag-only (VBO) processing of prepregs. In this study, the effects of pre-cure dwell temperature (debulk) on air evacuation were investigated for both plain weave (PW) and unidirectional (UD) prepregs. In situ observations revealed that increasing dwell temperature promoted inter-ply air evacuation (by as much as 2x for UD prepregs). Through-thickness gas permeability increased with increasing temperature and decreased with increasing number of plies. The decrease in in-plane permeability during heated debulk was attributed to increased tow impregnation. The findings provide guidelines for cure cycle optimization. Heated debulk enhanced air evacuation in PW laminates, particularly as laminate width/thickness ratios exceed a threshold value. However, warm debulks were less effective, particularly for thicker laminates (>8 plies). Graphical abstract: